The Cambridge handbook on law and policy for NFTs / edited by Nizan Geslevich Packin. - Packin, Nizan Geslevich, 1981- (Cambridge University Press, 2024)
As blockchain in general and NFTs in particular reshape operation logistics, data creation, and data management, these technologies bring forth many legal and ethical dilemmas. This handbook offers a comprehensive exploration of the impact of these technologies in different industries and sectors including finance, anti-money laundering, taxation, campaign-finance, and more. The book specifically provides insights and potential solutions for cutting-edge issues related to intellectual property rights, data privacy and strategy, information management, and ethical blockchain use, while offering insights, case studies, and recommendations to help anyone seeking to shape effective, balanced regulation to foster innovation while safeguarding the interests of all stakeholders. This handbook offers readers an invaluable roadmap for navigating the dynamic and evolving landscape of these new technologies.